The assessment of athletic equity by head men’s and women’s coaches in the National Junior College Athletic Association - Mullis, Riann (Kansas State University, 2024)
Throughout history, the foundation of athletics has remained consistent to provide the opportunity to compete and gain skills that will remain valuable throughout life. A significant change for athletics was over 50 years since President Richard Nixon signed Title IX of the Education Amendment (Title IX) into law in 1972 (Valentin, 1997). The purpose of this study was to aim to identify the current state and best practices of athletic equity implementation at National Junior College Athletic Association (NJCAA) DI and DII institutions. This study was composed of a mix-methods design that included a survey and interviews with head coaches of the following sports: men’s and women’s soccer, men’s and women’s basketball, men’s and women’s outdoor track and field, baseball, and softball to learn how head coaches assess athletic equity and identify best practices of athletic equity implementation. The findings of this study offer a unique perspective on how head coaches identify and assess athletic equity and best practice concepts that can be used for community college administrations nationwide to assist in the advancement of athletic equity.
Keywords: Athletic equity; Title IX; National Junior College Athletic Association; Head coaches; Best practices; Assessment